Global funding trends for malaria research in sub-Saharan Africa: a systematic analysis - Dr Michael G Head, PhD; Sian Goss, MSc; Yann Gelister, MSc; Victor Alegana, PhD; Rebecca J Brown, PhD; Stuart C Clarke, FFPH; Joseph R A Fitchett, MBBS; Prof Rifat Atun, FRCP; Prof J Anthony G Scott, PhD; Prof Marie-Louise Newell, PhD; Prof Sabu S Padmadas, PhD; Prof Andrew J Tatem, PhD (Elsevier, 2017)
Background: Total domestic and international funding for malaria is inadequate to achieve WHO global targets in burden reduction by 2030. We describe the trends of investments in malaria-related research in sub-Saharan Africa and compare investment with national disease burden to identify areas of funding strength and potentially neglected populations. We also considered funding for malaria control. Methods: Research funding data related to malaria for 1997-2013 were sourced from existing datasets, from 13 major public and philanthropic global health funders, and from funding databases. Investments (reported in US$) were considered by geographical area and compared with data on parasite prevalence and populations at risk in sub-Saharan Africa. 45 sub-Saharan African countries were ranked by amount of research funding received. Findings: We found 333 research awards totalling US$814·4 million. Public health research covered $308·1 million (37·8%) and clinical trials covered $275·2 million (33·8%). Tanzania ($107·8 million [13·2%]), Uganda ($97·9 million [12·0%]), and Kenya ($92·9 million [11·4%]) received the highest sum of research investment and the most research awards. Malawi, Tanzania, and Uganda remained highly ranked after adjusting for national gross domestic product. Countries with a reasonably high malaria burden that received little research investment or funding for malaria control included Central African Republic (ranked 40th) and Sierra Leone (ranked 35th). Congo (Brazzaville) and Guinea had reasonably high malaria mortality, yet Congo (Brazzaville) ranked 38th and Guinea ranked 25th, thus receiving little investment. Interpretation: Some countries receive reasonably large investments in malaria-related research (Tanzania, Kenya, Uganda), whereas others receive little or no investments (Sierra Leone, Central African Republic). Research investments are typically highest in countries where funding for malaria control is also high. Investment strategies should consider more equitable research and operational investments across countries to include currently neglected and susceptible populations. Funding: Royal Society of Tropical Medicine and Hygiene and Bill & Melinda Gates Foundation.